Miracle or magic in the Healing of the Blind One (Jo 9, 6-7): an epistemological commentary - Almeida, Maria Aparecida de Andrade; Funari, Pedro Paulo A. (Romanitas - Revista de Estudos Grecolatinos, 2017)
In John’s Gospel (9, 6-7) there is the story of healing of a blind born. It refers to Jesus as a healer, who sends the man to wash himself in the pool of Siloam (which is by interpretation, Sent.). He came back seeing for the first time. The Jewish authorities knew the blind man and they were struck by the miracle and they challenged him, saying that it was due to the Devil. This paper does not study Jesus power as a magician, shaman or otherwise, but explores the ways and means used to heal: magic or miracle?
Keywords: Magic; Miracle; Shamanism; Healing; Early Christianity